Fluorine-induced emission enhancement of tolanes via formation of tight molecular aggregates. (16th April 2020) - Morita, Masato; Yamada, Shigeyuki; Konno, Tsutomu
Abstract : Incorporation of fluorine atoms into the tolane backbone constructed tight crystal packing structures to suppress molecular motions, which provided dramatic enhancement of photoluminescence efficiency in crystalline state. Abstract : Fluorinated tolanes were found to show aggregation-induced emission characteristics and significantly enhanced photoluminescence efficiencies in molecular aggregates when compared with non-fluorinated tolanes. The fluorine atoms play important roles in the formation of tight crystal packing structures to suppress molecular motion in the crystalline state via electrostatic or hydrogen bonding interactions.